Primary squamous cell carcinoma of the rectum: a case report and literature review - Neil Vyas; Sumair Ahmad; Khaled Bhuiyan; Carmine Catalano; Hassan Alkhawam; Robert Sogomonian; James Nguyen; Aaron Walfish; Joshua Aron (Greater Baltimore Medical Center, 2016)
Squamous cell carcinoma (SCC) of the rectum is a rare occurrence with an incidence rate of 0.1-0.25% per 1,000 cases. Herein, we report a case of a 52-year-old female who presented with a 2-month history of diffuse lower abdominal pain and hematochezia. Abdominal CT scan revealed a 7-cm irregular rectal mass, and the biopsy showed SCC.